2020
DOI: 10.1186/s12903-020-01308-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of the oral microbiota in chronic non-communicable disease and its relevance to the Indigenous health gap in Australia

Abstract: Background Aboriginal Australians and Torres Strait Islanders (hereafter respectfully referred to as Indigenous Australians) experience disproportionately poor health and low life expectancy compared to non-Indigenous Australians. Poor oral health is a critical, but understudied, contributor to this health gap. A considerable body of evidence links poor oral health to increased risks of other chronic non-communicable conditions, such as diabetes, cardiovascular disease, chronic kidney disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 123 publications
(141 reference statements)
0
17
0
Order By: Relevance
“…Many host-related and environmental factors, including vertical transmission, diet, and antibiotic use have been reported to influence the diversity and composition of an individual's oral microbiota [17][18][19][20][21][22][23]. In turn, these factors may contribute to broader-scale microbiota differences among members of human groups with different heritage and lifestyles [24,25]. For example, studies from Venezuela, the Philippines and Uganda have reported differences in saliva microbiota diversity and composition between Indigenous groups with hunter-gatherer lifestyles and counterparts living agricultural or industrialized lifestyles [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Many host-related and environmental factors, including vertical transmission, diet, and antibiotic use have been reported to influence the diversity and composition of an individual's oral microbiota [17][18][19][20][21][22][23]. In turn, these factors may contribute to broader-scale microbiota differences among members of human groups with different heritage and lifestyles [24,25]. For example, studies from Venezuela, the Philippines and Uganda have reported differences in saliva microbiota diversity and composition between Indigenous groups with hunter-gatherer lifestyles and counterparts living agricultural or industrialized lifestyles [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…For example, although there is still limited research regarding oral microbial diversity among Indigenous groups, analyses of oral microbiota from Native American individuals indicated that the microbial communities of Indigenous participants significantly differed from their non-native counterparts, including high abundances of the genus Prevotella , which have been implicated in periodontal disease ( 68 ). In addition, it is also established that Aboriginal Australians and Torres Strait Islanders also suffer from higher incidences of NPDs and NCDs than their non-Indigenous counterparts ( 69 ). Recent research suggests that this health disparity may be complicated by the higher prevalence of oral disease, such as tooth decay and moderate to severe periodontal disease, experienced by Indigenous Australians in comparison to non-Indigenous Australians ( 69 ).…”
Section: Anthropological Insights Into Microbiome Research With Impli...mentioning
confidence: 99%
“…In addition, it is also established that Aboriginal Australians and Torres Strait Islanders also suffer from higher incidences of NPDs and NCDs than their non-Indigenous counterparts ( 69 ). Recent research suggests that this health disparity may be complicated by the higher prevalence of oral disease, such as tooth decay and moderate to severe periodontal disease, experienced by Indigenous Australians in comparison to non-Indigenous Australians ( 69 ). These systemic differences were correlated with established differences microbial diversity and composition of Indigenous and non-Indigenous Australians, suggesting that these differences in oral microbiota-related diseases may be specific to Indigenous Australians via a unique oral microbiome ( 69 ).…”
Section: Anthropological Insights Into Microbiome Research With Impli...mentioning
confidence: 99%
See 1 more Smart Citation
“…The oral microbiota refers to the collection of microorganisms that inhabit the oral cavity in different locations, such as the tongue, saliva and teeth [ 7 ]. Saliva has been shown to be a biological material capable of reflecting the dynamics of health conditions and metabolic, immunological or infectious diseases, reflecting dysbiosis of local and systemic origin, as observed in dental caries, periodontal diseases, diabetes, rheumatoid arthritis [ 8 ], cancer and, more recently, SARS-COV-2 [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%